Effectiveness of Planned Teaching Program Regarding Polycystic Ovarian Disease in Terms of Knowledge and Attitude among Students of SGT University - Syed Umaisa; Akoijam Mamata Devi; Sarika Yadav; Haobijam Madhubala Devi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The modernized technology has changed the daily lifestyle of human beings. An unhealthyeating habits and lack of exercise leads to occurrence of many diseases among adolescence. The currentstudy is here about the common disease i.e. polycystic ovarian disease (POCD) among women which causeto improper diet or hormonal balance this is due to lack of knowledge and irregular exercises.Objectives: The objectives of the study have drawn to fulfill the research reflecting on the effectivenessof planned teaching programme regarding polycystic ovarian disease (PCOD) in terms of knowledge andattitude among students of SGT University, GurugramMaterials and Method: In this study Pre-Experimental design was used to assess the effectiveness ofplanned teaching programme in terms of knowledge and attitude regarding polycystic ovarian disease(PCOD). Convenience sampling technique was used to select 60 students of SGT University, Gurugram. Astructured was administered to assess the knowledge and attitude. The collected data was analyzed by usingdescriptive and inferential statistics.Results: The comparison of pre and post test of knowledge score on polycystic ovarian syndrome to assessthe effectiveness of planned teaching programme improving the knowledge regarding polycystic ovariansyndrome among 60 students. The mean pre-test is 9.38 and post-test knowledge score 26.62 having asignificant difference with t value for knowledge is 12.85 at the level of significant p<0.05.Conclusion: It is concluded that that the planned teaching program was effective in improving the knowledgeand attitude regarding PCOD among students of SGT University.Therefore, it is recommended thatprecautionary measures can be adopted by female such as doing regularexercises to prevent PCOD for better health and each woman should have proper knowledge regardingPCOD in order to take prevention timely.